2003
DOI: 10.1074/jbc.m210578200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of ERK and Elk by Protein Kinase B Modulates c-fos Transcription

Abstract: In this study, we have identified novel regulatory steps involved in the cross-talk between protein kinase B (PKB) and MAPK signaling pathways. We found that PKB down-regulates the Ras-Raf-MEK-ERK pathway by reducing the activity of ERK, which leads to inactivation of the transcription factor Elk1. In addition, PKB is able to reduce protein levels of Elk1. Both events lead to suppression of serum response element (SRE)-dependent transcription and a consequent decrease in the transcription of SRE-containing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…In contrast, this result suggests that Akt acted downstream of ERK1/2 activation in the cytosol. In agreement with our data, a recent study reported that constitutively active Akt does not modify ERK1/2 phosphorylation (Galetic et al, 2003). In our study, the inhibition of ERK1/2 nuclear activity by overexpressed Akt resulted in a decrease in Elk-1-dependent transcription with a subsequent abolition of cFos expression.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, this result suggests that Akt acted downstream of ERK1/2 activation in the cytosol. In agreement with our data, a recent study reported that constitutively active Akt does not modify ERK1/2 phosphorylation (Galetic et al, 2003). In our study, the inhibition of ERK1/2 nuclear activity by overexpressed Akt resulted in a decrease in Elk-1-dependent transcription with a subsequent abolition of cFos expression.…”
Section: Discussionsupporting
confidence: 82%
“…Proteins (60 g) were separated by SDS-PAGE and immunoblotted with anti-phospho-ERK and anti-Akt antibody, respectively. regulate the Elk-1 transcription factor by decreasing either its expression (Figueroa and Vojtek, 2003) or its activation (Galetic et al, 2003). Therefore, the critical step for the negative regulation of ERK1/2 by Akt lies between the cytosolic activation of ERK1/2 and its activity on nuclear substrates, such as Elk-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Studies in human glioblastoma cells show: (i) protein kinase B inhibits Elk-1 expression by downregulation of the MEK-ERK pathway; 73 and (ii) activation and nuclear translocation of ERK1/2 induces activation of Elk-1. 74 Parallel with these findings, 73,74 we demonstrated that the reduction of ERK1/2 phosphorylation by RAMH results in decreased Elk-1 phosphorylation.…”
Section: Histamine Regulation Of Cholangiocyte Growthsupporting
confidence: 67%
“…Although c-fos expression was maintained at an elevated level through a mechanism independent of increased MAPK activity, constitutive SRE activity could be either because of deficient antagonistic phosphatase function (59,60) or by stimuli-independent phosphorylation by other kinases (61). Alternatively, SRE activity could be also regulated by a pathway involving the Rho family GTPases (62).…”
Section: Discussionmentioning
confidence: 99%